2019
DOI: 10.3233/jad-180914
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Phenotype of Vascular Cognitive Impairment in Patients with Type 2 Diabetes Mellitus

Abstract: The clinical phenotype of vascular cognitive impairment in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…A possible limitation of the study is that we obtained a measure of overall CBF at the level of the large extracranial arteries using two-dimensional phase-contrast MRI and did not measure CBF at the tissue level. Yet, the observed mean CBF values in our study are comparable to other studies that did use measures at the tissue level [1][2][3][4][5][6][7][8][9][10][11][12][13]. This does not exclude that there can be regional areas of abnormal perfusion at the site where lesions develop or have developed.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A possible limitation of the study is that we obtained a measure of overall CBF at the level of the large extracranial arteries using two-dimensional phase-contrast MRI and did not measure CBF at the tissue level. Yet, the observed mean CBF values in our study are comparable to other studies that did use measures at the tissue level [1][2][3][4][5][6][7][8][9][10][11][12][13]. This does not exclude that there can be regional areas of abnormal perfusion at the site where lesions develop or have developed.…”
Section: Discussionsupporting
confidence: 84%
“…We found no relationship between CBF and MBs or lacunes after correction for age and sex in our primary or secondary analyses. A limited number of studies, both cross-sectional and longitudinal, have assessed the association between CBF and these features of SVD [5][6][7][8][9][10][11][12][13]. A single study on MBs, in a rather small and selected population of patients with symptomatic SVD, did show a relationship between multiple MBs (5 or more) and lower CBF in one of several brain regions tested [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogama et al [28] found that postprandial hyperglycemia is related to WMH in diabetic patients with Alzheimer's disease while diabetic patients without dementia appeared to be less susceptible to the effects of hyperglycemia. Lacunar infarcts have been seen in patients with prediabetes and at an even higher number in patients with type 2 diabetes mellitus [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The automated segmentations for total brain, white/gray matter, and WMH volumes were subsequently corrected for manually created segmentations of infarcts or hemorrhages and incidental findings (eg, meningioma). A total of 823 (95.7%) scans passed quality control and were evaluated through the pipeline 27 …”
Section: Methodsmentioning
confidence: 99%